The Lifework of Architect Antonio A. Flores - Lanyi, Br. Bela S. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment, 2023)
Antonio Andres Legaspi Flores, a Filipino architect and educator, strongly shaped the built environment of his clients, mostly the Society of the Divine Word (SVD). It is now time to revisit his buildings, the motivations behind them, and their acceptance by investors and users. Up to today, the person of Flores is under debate. The paper examines Flores’ major design ideas and debated solutions where design advocacy seemed to contrast with physical sustainability. In conclusion, the research presents Flores’ lifework as an out-of-the-box approach that widens perspectives of Philippine architecture.